Face mask contamination during Covid-19 pandemia. A study on patients receiving intravitreal injections - Marín-Nieto, Juan; Reino-Perez, Carmen; Santillana-Cernuda, Genoveva; Díaz-Bernal, José Manuel; Luque-Aranda, Rafael; García Basterra, Ignacio (NLM (Medline), 2022)
PURPOSE: To investigate the bacterial growth in the surgical face masks used by patients who received intravitreal injections and study the effect of povidone-iodine on the periocular area (PA) of masks. METHODS: Forty patients who attended for intravitreal injections were divided in those with less ([removed]4 hours) than 4 hours of mask use. Each group was divided depending on the application or not of povidone-iodine in the PA of the mask. Bacterial load was studied on PA and mouth area samples. RESULTS: The bacterial load in the PA was higher in the >4 hours group compared with the [removed]4 hours group (P = 0.01). The use or not of povidone-iodine was strongly correlated to a positive culture (OR = 9.0, P = 0.00. CI 1.63-49.44). CONCLUSION: Surgical face masks worn for more than 4 hours present higher contamination in the PA than those with less use. Bacterial load in the PA is reduced with povidone-iodine on masks used for more than 4 hours. This contamination should be considered in the asepsis protocol of intravitreal injections.
Keywords: asepsis protocol; Covid-19; endophthalmitis; face mask; intravitreal injection; povidone–iodine; Scopus; JCR